Evaluating the Effectiveness of Corporate Governance Mechanisms in Mitigating Earnings Management: A Literature-Based Review - Tuti Dharmawati; Hasbudin; Muh. Syaiful Saehu; Muh. Azdar Setiawan; Wulandari Pryangan (Institut Bisnis dan Informatika Kesatuan, 2025)
Earnings management remains a critical challenge for corporations, making strong corporate governance essential to ensure financial transparency and accountability. Grounded in Agency Theory, which posits that independent monitoring mechanisms can mitigate conflicts of interest between management and shareholders, this study examines the connection between audit committee independence and earnings management in publicly traded corporations. The study uses secondary data from scholarly publications, journals, and reports as part of a literature review that takes a qualitative approach. The important significance of independent oversight in improving the accuracy and integrity of financial statements is shown by key findings that show a decrease in earnings management is linked to a higher degree of audit committee independence. The article explains how independent audit committees help prevent financial reporting manipulations by reducing conflicts of interest and guaranteeing efficient oversight. These results highlight how crucial it is to improve corporate governance frameworks, especially in developing nations like Indonesia, where family ownership frequently compromises audit committee independence. The findings provide practical insights for regulators and policymakers to strengthen governance codes promoting audit committee independence, while offering guidance for corporate practitioners to enhance oversight effectiveness and financial reporting quality.